Long non-coding RNAs in humans: Classification, genomic organization and function - Barbara Chodurska; Tanja Kunej (Non-coding RNA Research)
Long non-coding RNAs (lncRNAs) regulate numerous biological functions in animals. Despite recent advances in lncRNA research, their structural and functional annotation and classification remain an ongoing challenge. This review provides a comprehensive overview of human lncRNAs, highlighting their genomic organization, mode of action and role in physiological and pathological processes. Subgroups of lncRNA genes are discussed using representative examples and visualizations of genomic organization. The HUGO Gene Nomenclature Committee (HGNC) categorizes lncRNAs into nine subgroups: (1) microRNA non-coding host genes, (2) small nucleolar RNA non-coding host genes, (3) long intergenic non-protein coding RNAs (LINC), (4) antisense RNAs, (5) overlapping transcripts, (6) intronic transcripts, (7) divergent transcripts, (8) long non-coding RNAs with non-systematic symbols and (9) long non-coding RNAs with FAM root systems. Circular RNAs (circRNAs) are a separate class that shares some characteristics with lncRNAs and are divided into exonic, intronic and intronic-exonic types. LncRNAs act as molecular signals, decoys, scaffolds and sponges for microRNAs and often function as competing endogenous RNAs (ceRNAs). LncRNAs are involved in various physiological and pathological processes, such as cell differentiation, p53-mediated DNA damage response, glucose metabolism, inflammation and immune functions. They are associated with several diseases, including various types of neoplasms, Alzheimer's disease and autoimmune diseases. A clear classification system for lncRNA is essential for understanding their biological role and for facilitating practical applications in biomedical research. Future studies should focus on drug development and biomarker discovery. As important regulators of various biological processes, lncRNAs represent promising targets for innovative therapies.